Bentuk dan Proses Penciptaan Karya Tari Abhimantra pada Kompetisi Festival Kesenian Indonesia 2023 di Denpasar Bali - Soemaryatmi, S.Skar., M.Hum; Anastasya Kusuma Wardani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The article entitled "The Process of Creating Abimantra Dance Works at the 2023 Indonesian Arts Festival (FKI) in Denpasar Bali", intends to explain analytically the process of creating dance works in the context of the 2023 FKI competition or competition which opens up opportunities for the best students at higher education institutes art, to emerge as a champion. Looking at the facts of the process of creating Abhimantra dance works created in the context of this competition, it is interesting to discuss scientifically because it opens up discourse to understand the form of the work and the process of its creation in the context of competitions, where the characters are always under psychological pressure to win, represent a group or institution, and creative in the narrow space of competition rules. The formulation of the problem in this paper is to question 1) the form of the Abhimantra Dance Work and 2) the process of creating the Abhimantra Dance Work. The article research method used is qualitative research with participant observation data mining because the author is a dancer in the Abhimantra work. This article uses Sumandiyo Hadi's analytical theory regarding the form and process of creating dance works and Ahimsa Putra's analytical theory regarding the text and context of artistic works. Through this article it is concluded that 1) Abhimantra dance works are dance works in the form of duets or pairs that use the concept of surrealist dance work originating from the development of Surakarta Style vocabulary, exploration of large volume movements, risky extreme movements, and exploration of supporting elements of choreography such as costumes. , make-up, lighting and music, 2) the creation of this dance work cannot be done freely because it has to follow the technical guidelines for the competition, and 3) psychologically the creation of this dance is under the pressure of the desire to win the competition and 4) the Abhimantra dance work has distinctive choreography in the context competition interests. The writing of this scientific article considers that, in the process of creating Abhimantra dance works, creativity must be devoted to more creative energy in order to be able to create successful dance works in the context of competitions.